Casanova [videorecording (DVD)] - Hallström, Lasse; Ledger, Heath, 1979-2008; Miller, Sienna, 1981-; Irons, Jeremy, 1948-; Platt, Oliver (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Casanova has to begin searching for a wife. He is a womanizer with many conquests and If he cannot show he is living a more respectable life, the Church will throw him out of Venice. He is quickly engaged to Victoria, a woman with a pure reputation. As soon as that is arranged, he meets Francesca, a feminist who hates all he stands for. He pretends to be someone else to get into her good graces, and soon finds out she is engaged to Papprizzio, a man whom she has never met. Meanwhile, arriving in Venice to find Casanova, is Pucci, one of the Vatican's most known and feared inquisitors. Francesca falls in love with Casanova, who is pretending to be the Lard king himself. Francesca's brother Donato is in love with Victoria and her mother Andrea wants Francesca to marry a man of substance.